PLASMON MODES IN A MULTILAYER STRUCTURE WITH 3-BILAYER GRAPHENE SHEETS - Nguyen Van Men; Dong Thi Kim Phuong; Vu Dong Duong (Tạp chí Khoa học Đại học Đà Lạt)
Recent research demonstrates that graphene has unique properties and applications in many technological fields. This paper presents results calculated within random phase approximation at zero temperature for collective excitations, an important characteristic of materials, in a three-layer structure consisting of three bilayer graphene sheets in an inhomogeneous background dielectric. Numerical calculations show that one optical and two acoustic branches exist in the system. The optical branch becomes overdamped quickly while the two acoustic branches continue and disappear at single-particle excitation boundaries. The increase in carrier density in the layers significantly decreases the frequencies of plasmon modes. The inhomogeneity of the background dielectric decreases the frequency of the higher branches but increases that of the lower branch. The effects of interlayer separation on plasmon modes are similar to those in homogeneous systems. Our results may provide more information and contribute to improving the theory of graphene.